Loneliness, subjective health complaints, and medicine use among Finnish adolescents 2006-2018 - Lyyra Nelli; Junttila Niina; Tynjälä Jorma; Villberg Jari; Välimaa Raili (SAGE PUBLICATIONS LTD, 2022)
Aims: Loneliness is an important public health challenge for all ages. This study reports time trends of loneliness among adolescents over a 12-year period and analyses the strength of the associations between loneliness, health complaints, and medicine use. Methods: Data were derived from the cross-sectional Finnish Health Behaviour in School-aged Children study conducted in 2006, 2010, 2014, and 2018. The study population is based on a random sample of schools with 20,444 participants aged 11-15 years. The trends were analysed with a Mantel-Haenszel test, and the strength of the associations was evaluated by mixed-effects logistic and linear regressions. Results: An increasing prevalence in frequent loneliness (2006: 11%; 2018: 15%) was evident over the 12-year study period, especially in girls and 15-year-olds. Among all adolescents, loneliness was associated with a higher risk of recurrent health complaints and medicine use to treat the corresponding health issues, especially nervousness (odds ratio 5.8) and sleeping difficulties (odds ratio 7.6). Conclusions: Adolescence is a period of higher risk of frequent loneliness and associated health complaints. In this study, loneliness was common among adolescence and an increasing trend of loneliness was observed between 2006 and 2018. Also, psychosomatic health complaints and medicine use were strongly associated with loneliness. Persistent loneliness is a significant health risk and failure to resolve loneliness before entering adulthood may imply significant concerns for future well-being.